A fungal milRNA mediates epigenetic repression of a virulence gene in Verticillium dahliae. (14th January 2019) - Jin, Yun; Zhao, Jian-Hua; Zhao, Pan; Zhang, Tao; Wang, Sheng; Guo, Hui-Shan
Abstract : MiRNAs in animals and plants play crucial roles in diverse developmental processes under both normal and stress conditions. miRNA-like small RNAs (milRNAs) identified in some fungi remain functionally uncharacterized. Here, we identified a number of milRNAs in Verticillium dahliae, a soil-borne fungal pathogen responsible for devastating wilt diseases in many crops. Accumulation of a V. dahliae milRNA1, named VdmilR1, was detected by RNA gel blotting. We show that the precursor gene VdMILR1 is transcribed by RNA polymerase II and is able to produce the mature VdmilR1, in a process independent of V. dahliae DCL (Dicer-like) and AGO (Argonaute) proteins. We found that an RNaseIII domain-containing protein, VdR3, is essential for V. dahliae and participates in VdmilR1 biogenesis. VdmilR1 targets a hypothetical protein-coding gene, VdHy1, at the 3′UTR for transcriptional repression through increased histone H3K9 methylation of VdHy1 . Pathogenicity analysis reveals that VdHy1 is essential for fungal virulence. Together with the time difference in the expression patterns of VdmilR1 and VdHy1 during fungal infection in cotton plants, our findings identify a novel milRNA, VdmilR1, in V. dahliae synthesized by a noncanonical pathway that plays a regulatory role in pathogenicity and uncover an epigenetic mechanism for VdmilR1 in regulating a virulence target gene. This article is part of the theme issue 'Biotic signalling sheds light on smart pest management'.